Anti-Salmonella Activity of Thymus serpyllum Essential Oil in Sous Vide Cook–Chill Rabbit Meat - Miroslava Kačániová; Natália Čmiková; Maciej Ireneusz Kluz; Boutheina Ben Akacha; Rania Ben Saad; Wissem Mnif; Bożena Waszkiewicz-Robak; Stefania Garzoli; Anis Ben Hsouna (Foods, 2024)
Food is generally prepared and vacuum-sealed in a water bath, then heated to a precise temperature and circulated in a sous vide machine. Due to its affordability and ease of use, this cooking method is becoming increasingly popular in homes and food service businesses. However, suggestions from manufacturers and chefs for long-term, low-temperature sous vide cooking raise questions about food safety in the media. In this study, heat treatment with different times and wild thyme essential oil (EO) in sous vide-processed rabbit longissimus dorsi muscle were found to inactivate Salmonella enterica. The rabbit meat samples were vacuum-packed in control groups, in the second group the rabbit meat samples were injected with S. enterica, and in the third group were meat samples infected with S. enterica with Thymus serpylum EO additive. The vacuum-packed samples were cooked sous vide for the prescribed time at 55, 60, and 65 °C. At 5, 15, 30, and 60 min, the quantities of S. enterica, total bacterial counts, and coliform bacteria were measured in groups of sous vide rabbit meat. Microbiological analyses of rabbit meat samples on days 1 and 7 were evaluated. In this study, total viable counts, coliforms bacteria, and number of Salmonella spp. were identified. After incubation, isolates from different groups of microorganisms were identified by the mass spectrometry technique. For each day measured, the test group exposed to a temperature of 55 °C for 5 min had a greater number of total microbiota. The most isolated microorganisms by MALDI-TOF MS Biotyper from the control and treated groups were Lactococcus garvieae and in the treated groups also S. enterica. Based on our analysis of sous vide rabbit meat samples, we discovered that adding 1% of thyme essential oil to the mixture reduced the amount of Salmonella cells and increased the overall and coliform bacterial counts. The microbiological quality of sous vide rabbit meat that was kept for seven days was positively impacted by the addition of thyme essential oil.